Performance evaluation of an "m" shaped SCM wall in reinforcement of pile-supported wharf under yard heaped loads with centrifuge modelling. (15th August 2019) - Yan, Z.; Chen, Y.; Sun, X.P.; Zhang, H.Q.
Highlights: An "m" wall was proposed for a pile-supported wharf under yard heaped loads. Comparative centrifugal model tests on the effect of the "m" wall were conducted. Performances of the bent with and without the "m" wall were investigated. Mechanism of the "m" wall in reinforcing the pile-supported wharf was discussed. Abstract: Under excessive yard heaped loads, slopes are deformed, and piles are inclined, which may lead to the catastrophic failure of a pile-supported wharf. In this paper, centrifugal model tests were conducted to examine the effect of a newly proposed "m" shaped soil cement mixing (SCM) wall in the reinforcement of a pile-supported wharf. The "m" wall was constructed in the connecting section between the bent and loading yard. The performances of the bent with and without the "m" wall under yard heaped loads, i.e., the bent displacements, bending moments of the piles and earth pressures ahead of the piles, were compared to illustrate the reinforcement effects. The mechanism of the "m" wall in reinforcing the pile-supported wharf was also discussed. Test results indicate that the bent displacements were lessened and the ultimate bearing yard heaped loads increased with the "m" wall. The "m" wall reduced the bending moments of the piles, particularly in the middle and rear sections of the bent. The earth pressures ahead of piles were generally lower with than without the "m" wall. The "m" wall limited the integral translation of the slope induced by the yard heaped loads; thus, the compression of the surrounding soil to the piles was relieved, effectively protecting the bent from destruction.